IDENTITY AND LOCAL RELIGIOUS TRADITION OF THE AL-MANDARI COMMUNITY: A STUDY OF TAREKAT THE ANNANGGURU SAYYE’ DAENGNA MA’RUFI AL-MANDARI - Muhammad Ikhsan Saidung; Riza Muhammad; Salsabila, Fakhrina (Balai Penelitian dan Pengembangan Agama Jakarta, 2025)
The development of religious teachings often becomes the identity of a particular community, combining religious teachings with local culture. This study aims to reveal the Islamic-based education system through the concept and development of Sufi teachings in the Khalwatiyah Order developed by a figure named Annangguru Sayye' Daengna Ma'rufi al-Mandari in Mandar. This study uses a qualitative approach through interviews, literature studies and historical analysis of the texts and oral traditions of the order. The results of the study show that Annangguru's teachings are based on the Khalwatiyah Yusuf network and have undergone cultural adaptation with Mandar traditions. The education system he developed is built hierarchically through three levels of students, including: ana'guru malolo, ana'guru tangnga, and ana'guru matoa, with a focus on teaching zikr, morals, and spiritual awareness. This educational model not only shapes the inner dimension of a student, but also has implications for the moral and social development of society. This order is expected to become an example of local-based Sufi education that harmoniously integrates spiritual, cultural, and social aspects.